The failure of child support : gendered systems of iInaccessibility, inaction and irresponsibility / Kay Cook. - Cook, Kay (Policy Press, 2022)
Drawing on interviews with key international informants across sixteen countries, this book examines how child support systems often fail to transfer payments from separated fathers to mothers and their children. It identifies how the gender order is entrenched through child support failure and offers possibilities for feminist reform.